Correlation of Cigarette Smoking and Salted Fish Consumption with Nasopharyngeal Carcinoma and Its Clinical Stage in ORL-HNS Outpatient, Sanglah General Hospital - I Gde Ardika Nuaba; Tince Sarlin Nalle; I Wayan Weta (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma (NPC), which is located behind the nose, is the most common cancer. The causal of NPC is multifactorial including cigarette smoking and salted fish consumption. Objective: To determine the correlation between cigarette smoking and salted fish consumption with NPC and its clinical stage in the ENT-HNS outpatient, Sanglah General Hospital Denpasar. Methods: A case control study design in ENT clinic of Sanglah Hospital Denpasar. NPC is diagnosed by histopathology laboratory, and the stage of NPC using AJCC 8th, control criteria using policlinic ENT outpatient without cancer. Data were collected by interview method using a questionnaire on 46 patients who were confirmed NPC and 46 control groups. Then investigated the risk factors for cigarette smoking and consumption of salted fish. Results: The mean age of the NPC patient was 47.35±11.89 year old and the control group was 48.04 ±10.28 year old (P=0.130), likewise the composition of gender no statistically different between both groups (P=0.21. The risk (OR) of cigarette smoking and salted fish consumption on nasopharyngeal carcinoma patient was 4.7 (P<0.01) and 2.4(P=0.036), respectively. The results of multivariate analysis showed that there was a significant relationship between cigarette smoking to clinical stage of nasopharyngeal carcinoma (P=0.020 and AOR 3.364). Otherwise, there was no significant correlation between the consumption of salted fish, clinical stage of nasopharyngeal carcinoma (P=0.148 and AOR 2.288). Conclusion: It was found a significant association between cigarette smoking to nasopharyngeal carcinoma and its clinical stage, but not found any significant correlation between the consumption of salted fish with nasopharyngeal carcinoma.